Arthroscopic Treatment of Ankle Anterior Bony Impingement: The Long-term Clinical Outcome. (February 2014) - Parma, Alessandro; Buda, Roberto; Vannini, Francesca; Ruffilli, Alberto; Cavallo, Marco; Ferruzzi, Alberto; Giannini, Sandro
Background: Arthroscopic treatment of anterior ankle bony impingement provides good results, with a tendency to decrease over time. The purpose of this study was to analyze the factors affecting long-term results. Methods: Eighty consecutive patients with a mean age of 37.3 years were treated between 2000 and 2004. Impingement lesions were identified according to Scranton-McDermott classification. Preoperative ankle osteoarthritis was documented by van Dijk scale upon the x-rays. Bone spurs were analyzed and classified according to location and size. The associated chondral lesions were classified following the International Cartilage Repair Society (ICRS) criteria. Patient data, foot morphology, and previous traumas were recorded. Patients were evaluated after a mean of 104.6 months follow-up with the American Orthopaedic Foot and Ankle Society (AOFAS) scale. The influence of different factors on outcomes was statistically analyzed. Results: The mean preoperative AOFAS score was 50.9, while at follow-up it was 70.7 ( P < .05). The different grades of Scranton-McDermott impingement classification did not affect the results, but the different grades of van Dijk scale significantly affected the result but not the preoperative stage. Tibial localized spurs had better outcome at follow-up. The grade of the chondral lesions significantly affected the outcome. Other factors negatively affecting the results were age, cavus foot morphology, and history of previous ankle fracture. Conclusion: Arthroscopic treatment provides overall good results, but the long-term presence of associated conditions such as chondral lesions, advanced age, and previous trauma are relevant as prognostic factors. Based on these results, a new classification for bony impingement syndrome system is proposed. Level of Evidence: Level IV, case series.